Uniform spatial pooling explains topographic organization and deviation from receptive-field scale invariance in primate V1 - Y. Chen (Nature Portfolio, 2020)
Two-photon imaging in macaque V1 captured maps of tuning selectivity for four spatial parameters, all of which correlated with peak spatial frequency. These inter-map relationships reveal a common motif—they are described by uniform spatial pooling from a family of scale invariant Gabor receptive fields.